Time course of selective attention to face regions in social anxiety: eye-tracking and computational modelling - Calvo, Manuel G.; Gutiérrez-García, Aida; Fernández-Martín, Andrés (Cognition and Emotion, 2019)
We investigated the time course of selective attention to face regions during judgment of dis/approval by low (LSA) and high (HSA) social anxiety undergraduates (with clinical levels on questionnaire measures). The viewers’ gaze direction was assessed and the stimulus visual saliency of face regions was computed, for video-clips displaying dynamic facial expressions. Social anxiety was related to perception of disapproval from faces with an ambiguous smile (i.e. with non-happy eyes), but not those with congruent happy eyes and a smile. HSA observers selectively looked earlier at the eye region, whereas LSA ones preferentially looked at the smiling mouth. Consistently, gaze allocation was less related to visual saliency of the smile for HSA than for LSA viewers. The attentional bias towards the less salient eye region–thus opposing the automatic capture by the smile–suggests that it is strategically driven in HSA individuals, possibly aimed at detecting negative evaluators.
Keywords: eye movements; facial expression; perception of disapproval; social anxiety; visual saliency; Scopus; JCR